2014
DOI: 10.4028/www.scientific.net/amr.936.1273
|View full text |Cite
|
Sign up to set email alerts
|

Study on Wear Behaviors of Ni<sub>3</sub>Al/Cr-Carbides Cladding Layer on High Strength Steel Substrate

Abstract: A cladding layer of Ni3Al matrix composite reinforced with 18 vol. % Cr-carbides was applied by using tungsten inert gas (TIG) welding process on high strength steel substrate. The filler metal as welding wire prepared by horizontal continuous casting process with a composition of Ni-2.5C-30Cr-9Al-0.02B (in wt. %) is used. A bulk material of NAC-alloy composite with 18 vol. % Cr3C2-particles produced by Hot Isostatic Pressing (HIP) was also investigated as a reference material. The composition of NAC-alloy is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 9 publications
0
5
0
Order By: Relevance
“…Recent studies have indicated that the high-temperature mechanical strength and hardness of Ni 3 Al alloys can be significantly improved by the addition of hard-particle reinforcements [11][12][13]. When present in iron, cobalt, and nickel matrices, chromium carbide exhibits high hot-hardness and excellent hightemperature oxidation resistance combined with good wetting ability [14][15]. Hence, chromium carbides are chosen frequently as hard-particle reinforcements for addition into Ni 3 Al-based matrices, to form Cr 3 C 2 /Ni 3 Al composites [8,16].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent studies have indicated that the high-temperature mechanical strength and hardness of Ni 3 Al alloys can be significantly improved by the addition of hard-particle reinforcements [11][12][13]. When present in iron, cobalt, and nickel matrices, chromium carbide exhibits high hot-hardness and excellent hightemperature oxidation resistance combined with good wetting ability [14][15]. Hence, chromium carbides are chosen frequently as hard-particle reinforcements for addition into Ni 3 Al-based matrices, to form Cr 3 C 2 /Ni 3 Al composites [8,16].…”
Section: Introductionmentioning
confidence: 99%
“…Bullock et al [17] studied directionally solidified Ni-Ni 3 Al-Cr 3 C 2 composites and found that the composites show better creep resistance than the matrix-only material. The wear performance of chromium-carbide-reinforced Ni 3 Al matrix composites under ambient temperature was studied by Gong et al [15][16]18]. The results indicated that composites presented better wear resistance compared with the matrix-only material.…”
Section: Introductionmentioning
confidence: 99%
“…Related studies have shown [26] that under the same test conditions, there is a certain correlation between the hardness of materials and their wear performance. Furthermore, the variation in the hardness of the laser cladding layer can also reflect the distribution of carbides in the laser cladding layer.…”
Section: Effect Of Laser Power On Wear Resistance Of the Laser Claddi...mentioning
confidence: 98%
“…The rapid thermal process of laser cladding leads to non-equilibrium state of liquid solidification and, thus, an unequilibrium NiAl phase was formed. The NiAl phase may strengthen the Ni3Al matrix [33]. The residual coarse Cr3C2 in the mixed powder cladding layer is due to the large particle size of Cr3C2 in the mixed powder cladding layer, which only partially dissolves in the cladding layer [34].…”
Section: Microstructure and Phase Composition Of Cladding Layermentioning
confidence: 99%
“…EDS mapping of the alloyed powder cladding layer is shown in Figure 8. Considering the result of EDS mapping together with XRD analysis data, it can be determined that the black Cr and C elements containing rich phases could be a strengthening phase of Cr [33]. The residual coarse Cr 3 C 2 in the mixed powder cladding layer is due to the large particle size of Cr 3 C 2 in the mixed powder cladding layer, which only partially dissolves in the cladding layer [34].…”
Section: Microstructure and Phase Composition Of Cladding Layermentioning
confidence: 99%